The Evolution of the Enzyme Immunoassay/Enzyme-Linked Immunosorbent Assay - Leonid Tarassishin (Journal of Proteomics and Genomics Research, 2021)
50 years ago the Enzyme Immunoassay Enzyme-Linked Immunosorbent Assay, mostly known as ELISA was developed. This is a powerful but simple method that is very widely used in the diagnostic practice, as well as in biomedical research. During this time a number of ELISA modification were developed that significantly increased its properties, especially the senstivity, such as avidin-biotin assay, immuno-PCR, nano-ELISA and finally, the digital ELISA. This short review describes the principles of ELISA and the evolution from a conventional assay to the modern ultra-sensitive method. Most of the immunological methods have two components: antigen and antibody. The high specificity of their interaction gives a possibility to detect one of them if other one is included in the reaction as a specific partner. The simplest method for antigen detection in the presence of the antibody is immune diffusion (radial immune diffusion in that case), which practically the formation of precipitate of the “antigen-antibody” complex, when the target antigen diffuses from well into agarose containing the specific antibody. Unfortunately, this assay, as well as other traditional methods, like hemagglutination or complement fixation, have a low sensitivity and are unwieldy.
Keywords: Enzyme immunoassay